Bridging the Gap in Decoding Instruction: From Research to Explicit Teacher Training - Terra Xavier (Canadian Society for Studies in Education, 2022)
This article examines how the science of reading research is being applied to elementary teacher preparation programs in a Canadian province. Background information is explored regarding the research on the underlying failure of teacher preparation programs in embedding comprehensive decoding instruction in their course work. Three overarching themes from the research are described: 1) understanding language constructs is imperative; 2) effective preparation must involve robust coaching and mentoring; and 3) the Peter Effect impacting university instructors is a major barrier. By understanding and acknowledging the gap between the science of reading research and university programming, steps towards change can be made to improve teacher training and thereby improve student achievement.